Paano kita iibigin (Star Cinema, 2007)
Fired from her and evicted from her apartment, Marteena Diamzan (Regine Velasquez) brings herself and her son to a resort in Zambales. After an accidental damage caused by her son Martee is forced to worked as a manager under Lance Monteagudo (Piolo Pascual), the arrogant, alcoholic owner of the resort. Martee dislikes Lance so much and in all their interactions. they always clash. However, Martee soon learns the reason for Lance's personality disorder, and she begins to understand him. Difficult as it may seem, Martee helps Lance change his outlook in life. But an untimely meeting w/ people from his past reminds Lance of his guilt. He reverts to his old lifestyle. Shutting off Martee and her son from his life. This time, Martee is torn between letting go of a painful love or holding on to her one true love.